Thermal Stability in Closed House System in Optimizing Welfare and Productivity of Broiler Chickens in Tropical Climate - Ramadhan, Muh Rafli; Thiopelus, Angelin; Maulyda, Ishika; Pongkapadang, Kalvin N; Apada, Andi Magfira Satya; Yusuf, Subaedy; Marasakti, Rulli; Amal, Ichlasul (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to evaluate the Temperature Humidity Index (THI) in the Closed House system at PT. Anjas Farm and its impact on broiler chicken productivity. Data collection was carried out using the Elitech GSP 6 Temperature and Humidity Data Logger, which records temperature and humidity in real-time during the broiler chicken rearing period from DOC to week 5. The results showed an average THI of 23.5, with 93.84% of the time in the thermal comfort zone (THI < 24) and only 6.16% of the time showing mild to moderate thermal stress. This stability of THI supports the achievement of an average chicken weight of 2.8 kg, a feed conversion ratio (FCR) of 1.5–1.7, a low mortality of 4.2%, and optimal population density management. In conclusion, the Closed House system is effective in managing thermal conditions, increasing productivity, and supporting the welfare of broiler chickens. This research makes theoretical and practical contributions to the management of the thermal environment to support the efficiency of poultry farming in tropical climates. The results support the development of efficient and sustainable livestock technology.